The Influence Of Health Education On Increasing Self-Efficacy Of Post Partum Mothers At The UPT Ulaweng Public Health Center In 2023 - Syamsuriyati, Syamsuriyati; Syarif, Sutrani; Handayani, Rika; Prianti, Ani T (Sean Institute, 2024)
Health services for neonates (0-28 days) at least twice, once at the age of 0-7 days and one more time at the age of 8-28 days. The coverage of neonates visits in 2019 was 90.00%, decreasing in December 2020 by 85.00% (UPT Puskesmas Ulaweng). Providing Education Classes (KE) to Post Partum mothers using a module on the importance of breastfeeding for babies so that this can increase neonatal visits and the efficacy of mothers in breastfeeding their babies at the beginning of the postpartum period of 0-7 days through education . This study aims to determine the effectiveness of breastfeeding education class (KE) to increase the self-efficacy of post-partum mothers at the Ulaweng Public Health Center, Bone Regency in 2023. This type of research is a quasi-experimental design with a two group pretest-posttest design. The total sample size is 30 respondents (15 control group respondents who received a questionnaire without education class and 15 respondents in the intervention group who received education class and questionnaire). Samples were obtained using purposive sampling technique. Evaluation of maternal efficacy was carried out on the 7th day post partum both the control group and the intervention group.